Audio visual menjadi alat belajar yang memudahkan kegiatan belajar anak usia 5-6 tahun - Narang, Umriani R. (Maliki Interdisciplinary Journal, 2024)
In increasing understanding of children’s learning activities, an educator must choose the right learning media. Media is the plural of the word medium. The word medium is defined as an intermediary, conveying a message. In learning activities, media is a tool or means for sending messages or forms of communication to message recipients in the form of learning themes, ice breaking, moral messages and so on. Media in learning is very diverse, there is traditional media, semi-modern learning media and there is modern media. In the past, educators used pictures, posters and maps to explain. Nowadays, as times advance, educators explain learning via computers, laptops, projectors, cellphones, and so on. The media that educators can use nowadays is audiovisual media. One of the learning media that educators can use at this time is audiovisual media.